2022
DOI: 10.3389/fcell.2022.1049653
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide riboside kinases regulate skeletal muscle fiber-type specification and are rate-limiting for metabolic adaptations during regeneration

Abstract: Nicotinamide riboside kinases (NRKs) control the conversion of dietary Nicotinamide Riboside (NR) to NAD+, but little is known about their contribution to endogenous NAD+ turnover and muscle plasticity during skeletal muscle growth and remodeling. Using NRK1/2 double KO (NRKdKO) mice, we investigated the influence of NRKs on NAD+ metabolism and muscle homeostasis, and on the response to neurogenic muscle atrophy and regeneration following muscle injury. Muscles from NRKdKO animals have altered nicotinamide (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…A previous mouse study demonstrated that NR conversion to NAD + via NRKs is active in healthy muscle and NRKs regulate metabolic adaptations upon muscle regeneration 24 . However, Nrk2 plays a redundant role in basal muscle NAD + biosynthesis [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous mouse study demonstrated that NR conversion to NAD + via NRKs is active in healthy muscle and NRKs regulate metabolic adaptations upon muscle regeneration 24 . However, Nrk2 plays a redundant role in basal muscle NAD + biosynthesis [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous mouse study demonstrated that NR conversion to NAD + via NRKs is active in healthy muscle and NRKs regulate metabolic adaptations upon muscle regeneration 24 . However, Nrk2 plays a redundant role in basal muscle NAD + biosynthesis [24][25][26] . Interestingly, Nrk2 is typically upregulated during metabolic energy stress and NAD + deficiency to support NAD + production [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous preclinical studies have suggested that NR and NMN dietary supplements increase NAD + levels in the skeletal muscle and help protect musculoskeletal system from age-related metabolic dysfunction. NAD + biosynthesis pathways/homeostasis and its bioavailability in skeletal muscle cells are influenced by NAM phosphoribosyltransferase (NAMPT), NRK1, and NRK2 enzymes [ 118 , 119 ]. After the application of NRS in hexose-6-phosphate dehydrogenase KO (H6PDKO) mice, NAD + /NADH ratio was elevated but without any effect on insulin sensitivity, MT respiratory dysfunctions (MT acylcarnitine), acetyl coenzyme A metabolism and endoplasmic reticulum OXS [ 120 , 121 ].…”
Section: Effects Of Nicotinamide Riboside On Several Organs and Systemsmentioning
confidence: 99%
“…NMN is synthesized from NR via NRK-mediated phosphorylation, bypassing the need for NAMPT [15]. Mammals possess specific NRKs that function to synthesize NAD + via NMN in addition to the well-known pathways through NaMN [26].…”
Section: Salvage Pathwaymentioning
confidence: 99%